Vibrational Properties of the Potassium Titanyl Phosphate Crystal Family - Neufeld, Sergej; Gerstmann, Uwe; Padberg, Laura; Eigner, Christof; Berth, Gerhard; Silberhorn, Christine; Eng, Lukas M.; Schmidt, Wolf Gero; Rüsing, Michael (Crystals)
The crystal family of potassium titanyl phosphate (KTiOPO4) is a promising material group for applications in quantum and nonlinear optics. The fabrication of low-loss optical waveguides, as well as high-grade periodically poled ferroelectric domain structures, requires a profound understanding of the material properties and crystal structure. In this regard, Raman spectroscopy offers the possibility to study and visualize domain structures, strain, defects, and the local stoichiometry, which are all factors impacting device performance. However, the accurate interpretation of Raman spectra and their changes with respect to extrinsic and intrinsic defects requires a thorough assignment of the Raman modes to their respective crystal features, which to date is only partly conducted based on phenomenological modelling. To address this issue, we calculated the phonon spectra of potassium titanyl phosphate and the related compounds rubidium titanyl phosphate (RbTiOPO4) and potassium titanyl arsenate (KTiOAsO4) based on density functional theory and compared them with experimental data. Overall, this allows us to assign various spectral features to eigenmodes of lattice substructures with improved detail compared to previous assignments. Nevertheless, the analysis also shows that not all features of the spectra can unambigiously be explained yet. A possible explanation might be that defects or long range fields not included in the modeling play a crucial rule for the resulting Raman spectrum. In conclusion, this work provides an improved foundation into the vibrational properties in the KTiOPO4 material family.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Solid solutions of lithium niobate and lithium tantalate: crystal growth and the ferroelectric transition - Bashir, Umar; Böttcher, Klaus; Klimm, Detlef; Ganschow, Steffen; Bernhardt, Felix; Sanna, Simone; Rüsing, Michael; Eng, Lukas M.; Bickermann, Matthias (Ferroelectrics)
Specific heat capacity measurements by differential scanning calorimetry (DSC) of single crystals of solid solutions of LiNbO3 and LiTaO3 are reported and compared with corresponding ab initio calculations, with the aim to investigate the variation of the ferroelectric Curie temperature as a function of composition. For this purpose, single crystals of these solid solutions were grown with Czochralski pulling along the c-axis. Elemental composition of Nb and Ta was investigated using XRF analysis, and small samples with homogeneous and well known composition were used for the DSC measurements. We observed that the ferroelectric Curie temperature decreases linearly with increasing Ta concentration in the LiNb1−x Tax O3 solid solution crystals. Furthermore, the ferroelectric transition width of a mixed crystal appears to be smaller, as compared to pure LiTaO3.
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Learning the pronunciation of segmental features of english phonology at german primary schools - Hahn, Charlotte Anna
In der vorliegenden Arbeit wird die Auswirkung expliziter Ausspracheübungen auf die englische Aussprache von Kindern an Grundschulen in NRW untersucht. Das Ziel dieser Arbeit ist es, eine Alternative für den mittel-offenen vorderen Vokal /æ/ und die dentalen Frikative /, ð/ zu bieten. Es wurde eine Interventionsstudie mit 72 Teilnehmenden aus drei verschiedenen Grundschulklassen durchgeführt; zwei vierte Klassen mit verschiedenen Lehrkräften und eine dritte Klasse, die von der Lehrperson einer der vierten Klassen unterrichtet wurde. Jede Klasse wurde in eine Kontroll- und zwei Interventionsgruppen (je eine für den Vokal und die Konsonanten) geteilt. Alle Gruppen wurden einmal zu Beginn und zwei Mal am Ende der Studie getestet. Zwischen den letzten beiden Tests lagen sechs bis acht Wochen, um einen mittelfristigen Effekt zu testen. Die Intervention, die nach der ersten Messung stattfand, wurde auf zwei je ca. drei-minütige Einzelsitzungen aufgeteilt. Während der Intervention übten die Teilnehmenden mit der Autorin die Aussprache des relevanten Phonems. Die Ergebnisse dieser Studie zeigen, dass die Interventionen einen Effekt auf die Aussprache der Teilnehmenden hatten. Wie sich dieser Effekt verhält und entwickelt scheint von der Art des Phonems, dem Alter der Teilnehmenden sowie der bisherigen Ausspracheschulung abzuhängen. Die vorliegenden Ergebnisse liefern Erkenntnisse nicht nur für die Grundschule selbst, sondern auch für die Lehrer*innenausbildung und Lehrplanentwicklung.

Vorzeichenrichtige tomographische Rekonstruktion von Ultraschallfeldern mit Hilfe der Schlierentechnik - Hetkämper, Tim; Claes, Leander; Henning, Bernd (tm - Technisches Messen)
Keywords: Electrical and Electronic Engineering; Instrumentation

Systematics for an Integrative Modelling of Product and Production System - Schäfer, Louis; Günther, Matthias; Martin, Alex; Lüpfert, Mariella; Mandel, Constantin; Rapp, Simon; Lanza, Gisela; Anacker, Harald; Albers, Albert; Köchling, Daniel (Procedia CIRP)
Keywords: General Medicine

Virtual Assembly for Engineering – A Systematic Literature Review - Dyck, Florian; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Reibungsinduzierter Prozess zum nutzerindividuellen und energieeffizienten Recycling von Aluminiumschrotten - Borgert, Thomas
Die weltweit erzeugten Emissionen müssen in allen emittierenden Sektoren signifikant gesenkt werden, um die Auswirkungen des Klimawandels zu reduzieren. Dies ist unter anderem durch die energieeffiziente Wiederverwertung vorhandener Ressourcen und damit der Einstellung einer nachhaltigen Kreislaufwirtschaft möglich. Aufgrund der hohen erforderlichen Energiemenge in der primären Herstellung von Aluminium existieren hier im Vergleich zu anderen Konstruktionswerkstoffen große Einsparpotentiale. Mit dem in dieser Arbeit erforschten reibungsinduzierten Recyclingverfahren (RIR) wird eine alternative und energieeffiziente Prozessroute zum direkten Recycling von unterschiedlichen Aluminiumschrotten geschaffen. Zur Charakterisierung der Prozessroute werden u. a. die Erkenntnisse aus sich gegenseitig unterstützenden experimentellen und theoretischen Untersuchungen zu den Vorgängen der der Verdichtung, Plastifizierung als auch Extrusion der recycelten Profile dargelegt. Die Einflüsse unterschiedlicher Eingangsgrößen wie z. B. der Werkzeuggestaltung oder der Verarbeitung unterschiedlicher Legierungen werden zudem zur zukünftigen Auslegung des Prozesses erläutert. Aus der abschließenden energetischen Bilanzierung kann geschlossen werden, dass aufgrund der geringeren Verarbeitungstemperatur signifikante Energieersparnisse bei Verwendung des RIR im Vergleich zu den konventionellen Produktionsstrategien erzielt werden können.

Kinderladenbewegung: Auf den Spuren von Kinderladenkindern und ihren Eltern zwischen Laden, Garten und Natur. - Göddertz, Nina; Bock, Karin (Handbuch Kindheit, Ökologie, Nachhaltigkeit)

Kindermädchen – Von ‚strebsamen Mädchen‘, fliegenden Regenschirmen und neuen Gewändern eines (nicht) ausgestorbenen Berufes - Göddertz, Nina (Soziale Frauenberufe in Ost und West)

Dienstmädchen – von romantisierten Zuschreibungen und menschenunwürdigen Arbeits- und Lebensbedingungen, damals wie heute. - Göddertz, Nina (Soziale Frauenberufe in Ost und West)

Ein ‚bunter Blumenstrauß‘ an Praxisphasen. Gestaltungsaufgaben und Entwicklungsbedarfe in der Lehrer*innenbildung Sozialpädagogik. - Göddertz, Nina; Schmoekel, Michelle Jaquelina (Berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)

The Choice of Ideology and Everyday Decisions - Burs, Carina; Gries, Thomas; Müller, Veronika (Journal of Organizational Psychology)
Individuals strive to make decisions that are consistent with not only their consumer preferences but also their psychological needs. However, they are confronted with complex, ambiguous or even false information. Ideologies and belief systems provide guidance when processing and evaluating information and give a coherent and comprehensible interpretation of reality. The first question is: why is an individual attracted to a particular ideology? Individuals choose ideologies that resonate with their subjective psychological needs and preferences. Second, how do individuals search for ideologies and find out which suit them best? We model an individual’s sequential information search for the best matching ideologies by applying Bayesian learning and utility optimization. Additional information enhances utility by reducing uncertainty. As a search is costly, the process may stop once an individual adopts an ideology even if the information set remains incomplete. Third, once they have chosen a particular ideology, individuals adhere to its rules and norms when making everyday decisions. Consumers not only physically consume, but they also act in accordance with their psychological needs.
Keywords: Economics; Ideology; Decision-making

Erlebnisorientiert Lehren und Lernen in der beruflichen Bildung. Entwicklung eines didaktischen Konzepts im Rahmen von designbasierter Forschung. - Volgmann, Simone

Minisymposium Data Science - Podworny, Susanne; Frischemeier, Daniel (Beiträge zum Mathematikunterricht 2022: 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik vom 29.08.2022 bis 02.09.2022 in Frankfurt am Main)

Wege zu einer Didaktik der Sozialpädagogik
Wie kann sozialpädagogisches Handeln erlernt und gelehrt werden? Die Qualifizierungswege für sozialpädagogische Fachkräfte sind vielfältig, mitunter widersprüchlich und in verschiedenen Ebenen eingelagert, von Berufsfachschulen, Fachschulen, Fachhochschulen bis hin zu universitären Studiengängen. Ebenso vielfältig sind die beruflichen Anforderungen an sozialpädagogische Fachkräfte. Der Sammelband widmet sich den unterschiedlichen Zugängen zu einer Didaktik der Sozialpädagogik in Bezug auf die Bildungs-, Lern- und Qualifizierungsprozesse zukünftiger sozialpädagogischer Fachkräfte sowie Lehramtsstudierender mit der beruflichen Fachrichtung Sozialpädagogik.
Keywords: Ausbildung Kita-Fachkraft; Ausbildung Soziale Arbeit; Care-Berufe; didaktische Grundlagen; Erzieher*innen-Ausbildung; Erzieher-Ausbildung; Fachkräftemangel; Fachrichtung Sozialpädagogik; Lehramt Sozialpädagogik; schulische Ausbildung; soziale Berufe; Sozialpädagogik unterrichten; Sozialpädagogische Ausbildungsgänge; Sozialwesen; Unterricht Soziale Arbeit

A Social Network Approach for Investigating Social Influences on Effective Use: Demonstration in Virtual Reality Collaboration - Tölle, Laura; Slawinski, Elena; Fromm, Jennifer; Mirbabaie, Milad

Under Pressure? - The Effect of Conversational Agents on Task Pressure and Social Relatedness in Digital Labor - Lichtenberg, Sascha; Hildebrandt, Fabian; Mirbabaie, Milad

Understanding Digital Nomadism as an Employer Branding Signal - Marx, Julian; Langer, Marie; Mirbabaie, Milad

Model Predictive Direct Self-Control for Six-Step Operation of Permanent-Magnet Synchronous Machines - Pena, Mario; Meyer, Michael; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Differentially Private Natural Language Models: Recent Advances and Future Directions

How Much User Context Do We Need? Privacy by Design in Mental Health NLP Applications - Sawhney, Ramit; Neerkaje, Atula; Habernal, Ivan; Flek, Lucie (Proceedings of the International AAAI Conference on Web and Social Media)
Clinical NLP tasks such as mental health assessment from text, must take social constraints into account - the performance maximization must be constrained by the utmost importance of guaranteeing privacy of user data. Consumer protection regulations, such as GDPR, generally handle privacy by restricting data availability, such as requiring to limit user data to 'what is necessary' for a given purpose. In this work, we reason that providing stricter formal privacy guarantees, while increasing the volume of user data in the model, in most cases increases benefit for all parties involved, especially for the user. We demonstrate our arguments on two existing suicide risk assessment datasets of Twitter and Reddit posts. We present the first analysis juxtaposing user history length and differential privacy budgets and elaborate how modeling additional user context enables utility preservation while maintaining acceptable user privacy guarantees.

One size does not fit all: Investigating strategies for differentially-private learning across NLP tasks - Senge, Manuel; Igamberdiev, Timour; Habernal, Ivan (Proceedings of the 2022 Conference on Empirical Methods in Natural Language Processing)

DP-BART for Privatized Text Rewriting under Local Differential Privacy - Igamberdiev, Timour; Habernal, Ivan (Findings of the Association for Computational Linguistics: ACL 2023)

The Legal Argument Reasoning Task in Civil Procedure - Bongard, Leonard; Held, Lena; Habernal, Ivan (Proceedings of the Natural Legal Language Processing Workshop 2022)

Mining legal arguments in court decisions - Habernal, Ivan; Faber, Daniel; Recchia, Nicola; Bretthauer, Sebastian; Gurevych, Iryna; Spiecker genannt Döhmann, Indra; Burchard, Christoph (Artificial Intelligence and Law)
Abstract Identifying, classifying, and analyzing arguments in legal discourse has been a prominent area of research since the inception of the argument mining field. However, there has been a major discrepancy between the way natural language processing (NLP) researchers model and annotate arguments in court decisions and the way legal experts understand and analyze legal argumentation. While computational approaches typically simplify arguments into generic premises and claims, arguments in legal research usually exhibit a rich typology that is important for gaining insights into the particular case and applications of law in general. We address this problem and make several substantial contributions to move the field forward. First, we design a new annotation scheme for legal arguments in proceedings of the European Court of Human Rights (ECHR) that is deeply rooted in the theory and practice of legal argumentation research. Second, we compile and annotate a large corpus of 373 court decisions (2.3M tokens and 15k annotated argument spans). Finally, we train an argument mining model that outperforms state-of-the-art models in the legal NLP domain and provide a thorough expert-based evaluation. All datasets and source codes are available under open lincenses at https://github.com/trusthlt/mining-legal-arguments .
Keywords: Law; Artificial Intelligence

Faktor Mensch. Jahrbuch Technikphilosophie 2023
With the focus topic “The Human Factor”, the Jahrbuch Technikphilosophie 2023 aims to investigate on the one hand the manifold arrangements of the deficiency in the technical field (and especially “new” technologies): How do machine worlds, user interfaces, implementation strategies, or even entire large-scale technological ecosystems model, compensate, and even parody “the” human being – that is, “their” version of ourselves? How does technology discriminate? How does it educate? To what extent can it “reduce” the human? On the other hand, it is necessary to take a new look at what “human” actually means in precisely this context, and to reexamine anthropology as part of theories of technology and discourses on technology. Criticism of technology must therefore also be criticism of man. With contributions by Fabian Anicker, Petra Gehring, Axel Gelfert, Martina Heßler, Andreas Kaminski, Ruth Karl, Katerina Krtilova, Joachim Landkammer, Kevin Liggieri, Felix Maschewski, Nicola Mößner, Anna-Verena Nosthoff, Felix Reda, Jean Paul Sartre, Björn Schembera, Stefan Schöberlein, Marcel Siegler, Florian Sprenger and Martin Warnke.

Protein intake and type 2 diabetes mellitus: an umbrella review of systematic reviews for the evidence-based guideline for protein intake of the German Nutrition Society - Schulze, Matthias B.; Haardt, Julia; Amini, Anna M.; Kalotai, Nicole; Lehmann, Andreas; Schmidt, Annemarie; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Kühn, Tilman; Louis, Sandrine; et al. (European Journal of Nutrition)
Abstract Purpose Protein-rich foods show heterogeneous associations with the risk of type 2 diabetes (T2D) and it remains unclear whether habitual protein intake is related to T2D risk. We carried out an umbrella review of systematic reviews (SR) of randomised trials and/or cohort studies on protein intake in relation to risks of T2D. Methods Following a pre-specified protocol (PROSPERO: CRD42018082395), we retrieved SRs on protein intake and T2D risk published between July 1st 2009 and May 22nd 2022, and assessed the methodological quality and outcome-specific certainty of the evidence using a modified version of AMSTAR 2 and NutriGrade, respectively. The overall certainty of evidence was rated according to predefined criteria. Results Eight SRs were identified of which six contained meta-analyses. The majority of SRs on total protein intake had moderate or high methodological quality and moderate outcome-specific certainty of evidence according to NutriGrade, however, the latter was low for the majority of SRs on animal and plant protein. Six of the eight SRs reported risk increases with both total and animal protein. According to one SR, total protein intake in studies was ~ 21 energy percentage (%E) in the highest intake category and 15%E in the lowest intake category. Relative Risks comparing high versus low intake in most recent SRs ranged from 1.09 (two SRs, 95% CIs 1.02–1.15 and 1.06–1.13) to 1.11 (1.05–1.16) for total protein (between 8 and 12 cohort studies included) and from 1.13 (1.08–1.19) to 1.19 (two SRs, 1.11–1.28 and 1.11–1.28) (8–9 cohort studies) for animal protein. However, SRs on RCTs examining major glycaemic traits (HbA 1c , fasting glucose, fasting insulin) do not support a clear biological link with T2D risk. For plant protein, some recent SRs pointed towards risk decreases and non-linear associations, however, the majority did not support an association with T2D risk. Conclusion Higher total protein intake was possibly associated with higher T2D risk, while there is insufficient evidence for a risk increase with higher intakes of animal protein and a risk decrease with plant protein intake. Given that most SRs on plant protein did not indicate an association, there is possibly a lack of an effect.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Protein intake and body weight, fat mass and waist circumference: an umbrella review of systematic reviews for the evidence-based guideline on protein intake of the German Nutrition Society - Ellinger, Sabine; Amini, Anna M.; Haardt, Julia; Lehmann, Andreas; Schmidt, Annemarie; Bischoff-Ferrari, Heike A.; Buyken, Anette; Kroke, Anja; Kühn, Tilman; Louis, Sandrine; Lorkowski, Stefan; Nimptsch, Katharina; et al. (European Journal of Nutrition)
Abstract Purpose This umbrella review aimed to assess whether dietary protein intake with regard to quantitative (higher vs. lower dietary protein intake) and qualitative considerations (total, plant-based or animal-based protein intake) affects body weight (BW), fat mass (FM) and waist circumference (WC). Methods A systematic literature search was conducted in PubMed, Embase and Cochrane Database of Systematic Reviews for systematic reviews (SRs) with and without meta-analyses of prospective studies published between 04 October 2007 and 04 January 2022. Methodological quality and outcome-specific certainty of evidence of the retrieved SRs were assessed by using AMSTAR 2 and NutriGrade, respectively, in order to rate the overall certainty of evidence using predefined criteria. Results Thirty-three SRs were included in this umbrella review; 29 were based on randomised controlled trials, a few included cohort studies. In studies without energy restriction, a high-protein diet did not modulate BW, FM and WC in adults in general (all “possible” evidence); for older adults, overall certainty of evidence was “insufficient” for all parameters. Under hypoenergetic diets, a high-protein diet mostly decreased BW and FM, but evidence was “insufficient” due to low methodological quality. Evidence regarding an influence of the protein type on BW, FM and WC was “insufficient”. Conclusion “Possible” evidence exists that the amount of protein does not affect BW, FM and WC in adults under isoenergetic conditions. Its impact on the reduction in BW and FM under hypoenergetic conditions remains unclear; evidence for an influence of protein type on BW, FM and WC is “insufficient”.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Reverberation as Supervision For Speech Separation - Aralikatti, Rohith; Boeddeker, Christoph; Wichern, Gordon; Subramanian, Aswin; Le Roux, Jonathan (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Mixture Encoder for Joint Speech Separation and Recognition - Berger, Simon; Vieting, Peter; Boeddeker, Christoph; Schlüter, Ralf; Haeb-Umbach, Reinhold (INTERSPEECH 2023)

Investigating the potential of artificial intelligence for the employee from the perspective of AI-experts - Humpert, Lynn; Tihlarik, Amelie; Wäschle, Moritz; Anacker, Harald; Dumitrescu, Roman; Albers, Albert; Röbenack, Silke; Pfeifer, Sabine (IEEE International Conference on Technology Management, Operations and Decisions (IEEE ICTMOD))

Identification of fields of action for validation in Systems Engineering - Humpert, Lynn; Zagatta, Kristin; Anacker, Harald; Dumitrescu, Roman (IEEE International Conference on Technology Management, Operations and Decisions (IEEE ICTMOD))

Criteria-based comparison of Systems Engineering and agile methods - Humpert, Lynn; Mundt, Enrik; Bretz, Lukas; Bernz, Vanessa; Anacker, Harald; Dumitrescu, Roman (8th International Conference on Information Systems Engineering)

Strategic planning of the collaboration between humans and artificial intelligence in production - Gabriel, Stefan; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Principles for the effective application of Systems Engineering: A systematic literature review and application use case - Mundt, Enrik; Wilke, Daria; Anacker, Harald; Dumitrescu, Roman

Integration von Design Thinking in Systems Engineering mit Hilfe des Systemdenkens - Tekaat, Julian; Wilke, Daria; Anacker, Harald; Dumitrescu, Roman

Lydia Böttger (Universität Paderborn) rezensiert: Burwitz-Melzer, Eva; Riemer, Claudia; Schmelter, Lars (Hrsg.) (2022): Feedback beim Lehren und Lernen von Fremd- und Zweitsprachen. Arbeitspapiere der 42. Frühjahrs- konferenz zur Erforschung des Fremdsprachenunterrichts. [Giessener Beiträge zur Fremdsprachendidaktik]. Tübingen: Narr Francke Attempto, 245 Seiten. ISBN 978-3- 8233-8569-1 - Böttger, Lydia (www.daz-portal.de)

Alignment between timing of ‘highest caloric intake’ and chronotype in relation to body composition during adolescence: the DONALD Study - Jankovic, Nicole; Schmitting, Sarah; Stutz, Bianca; Krüger, Bettina; Buyken, Anette; Alexy, Ute (European Journal of Nutrition)
Abstract Purpose Our aim was to assess alignment in timing of ‘highest caloric intake’ with individual chronotype and its association with body composition in adolescents. Methods We used repeatedly collected data from n = 196 adolescents (age 9–16 years, providing N = 401 yearly questionnaires) of the DONALD open cohort study. Chronotype was assessed by the Munich Chronotype Questionnaire from which midpoint of sleep (MSFsc) was derived. A sex- and age-specific diet-chrono-alignment score (DCAS) was calculated as the difference in hours between the chronotype-specific median timing of highest caloric intake of the studied population and the individual timing of ‘highest caloric intake’ or vice versa. Repeated-measures regression models were applied to study cross-sectional and longitudinal associations between the DCAS and body composition, e.g., Fat Mass Index (FMI) or Fat Free Mass Index (FFMI). Results DCAS ranged from −6:42 h to + 8:01 h and was not associated with body composition. Among adolescents with a later chronotype ( N = 201) a 1 h increase in DCAS (later consumption of ‘highest caloric intake’ in comparison to the median intake of that group), increased FFMI by 1.92 kg/m 2 (95% CI: 0.15, 3.69, p value = 0.04) over a median follow-up of 0.94 year. Conclusion Alignment of energy intake with individual chronotype appears beneficial for FFMI among those with a late chronotype.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Re-examining the quality dimensions of synthetic speech - Seebauer, Fritz; Kuhlmann, Michael; Haeb-Umbach, Reinhold; Wagner, Petra (12th Speech Synthesis Workshop (SSW) 2023)

Verben in Szenen. Grammatikgespräche im Sprachvergleich - Topalović, Elvira; Blachut, Alisa (Grundschule Deutsch)

Professionelle Unterrichtswahrnehmung von Lehramtsstudierenden – das Projekt iDEAL. Vortrag auf der Herbsttagung 2023 der Arbeitsgruppe Empirische Sonderpädagogische Forschung (AESF) - Görel, Gamze; Finke, Pauline; Hellmich, Frank

Breaking Down Barriers: How Conversational Agents Facilitate Open Science and Data Sharing - Mirbabaie, Milad; Rieskamp, Jonas; Hofeditz, Lennart; Stieglitz, Stefan

From Virality to Veracity: Examining False Information on Telegram vs. Twitter - Rieskamp, Jonas; Mirbabaie, Milad; Langer, Marie; Kocur, Alexander

Practice reduces the costs of producing head fakes in basketball - Böer, Nils Tobias; Weigelt, Matthias; Schütz, Christoph; Güldenpenning, Iris (Psychological Research)
Abstract Previous research indicates that performing passes with a head fake in basketball leads to increased response initiation times and errors as compared to performing a pass without a head fake. These so-called fake production costs only occurred when not given the time to mentally prepare the deceptive movement. In the current study, we investigated if extensive practice could reduce the cognitive costs of producing a pass with head fake. Twenty-four basketball novices participated in an experiment on five consecutive days. A visual cue prompted participants to play a pass with or without a head fake either to the left or right side. The cued action had to be executed after an interstimulus interval (ISI) of either 0 ms, 400 ms, 800 ms or 1200 ms, allowing for different movement preparation times. Results indicated higher response initiation times (ITs) and error rates (ERs) for passes with head fakes for the short preparation intervals (ISI 0 ms and 400 ms) on the first day but no difference for the longer preparation intervals (ISI 800 ms and 1200 ms). After only one day of practice, participants showed reduced fake production costs (for ISI 0 ms) and were even able to eliminate these cognitive costs when given time to mentally prepare the movement (for ISI 400 ms). Accordingly, physical practice can reduce the cognitive costs associated with head-fake generation. This finding is discussed against the background of the strengthening of stimulus response associations.
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology; General Medicine

Die Bedeutung digitaler Medien für die unterrichtsbezogene Lehrerkooperation - erste Ergebnisse einer empirischen Studie - Engemann, Mario; Herzig, Bardo

Accelerating the analysis of optical quantum systems using the Koopman operator - Peitz, Sebastian; Hunstig, Anna; Rose, Hendrik; Meier, Torsten
The prediction of photon echoes is an important technique for gaining an understanding of optical quantum systems. However, this requires a large number of simulations with varying parameters and/or input pulses, which renders numerical studies expensive. This article investigates how we can use data-driven surrogate models based on the Koopman operator to accelerate this process. In order to be successful, we require a model that is accurate over a large number of time steps. To this end, we employ a bilinear Koopman model using extended dynamic mode decomposition and simulate the optical Bloch equations for an ensemble of inhomogeneously broadened two-level systems. Such systems are well suited to describe the excitation of excitonic resonances in semiconductor nanostructures, for example, ensembles of semiconductor quantum dots. We perform a detailed study on the required number of system simulations such that the resulting data-driven Koopman model is sufficiently accurate for a wide range of parameter settings. We analyze the L2 error and the relative error of the photon echo peak and investigate how the control positions relate to the stabilization. After proper training, the dynamics of the quantum ensemble can be predicted accurately and numerically very efficiently by our methods.

An IAD framework analysis of minigrid institutions for sustainable rural electrification in East Africa: A comparative study of Uganda and Tanzania - Namujju, Lillian Donna; Acquah-Swanzy, Henrietta; Ngoti, Irene F. (Energy Policy)
Keywords: Management; Monitoring; Policy and Law; General Energy

Thermo-hydraulic Performance of Pillow-Plate Heat Exchangers with Secondary Structuring: A Numerical Analysis - Afsahnoudeh, Reza; Wortmeier, Andreas; Holzmüller, Maik; XGong, Yi; Homberg, Werner; Kenig, Eugeny Y. (Energies)

Sure you are ready? Gendered arguments in recruitment for high-status positions in male-dominated fields - Dutz, Regina; Hubner-Benz, Sylvia; Emmerling, Franziska; Peus, Claudia (Frontiers in Psychology)
Recruitment contexts such as STEM professorships promote clearly defined selection criteria and objective assessment. We illuminate in these contexts, the subjective interpretation of seemingly objective criteria and gendered arguments in discussions of applicants. Additionally, we explore gender bias despite comparable applicant profiles investigating how specific success factors lead to selection recommendations for male and female applicants. Implementing a mixed methods approach, we aim to highlight the influence of heuristics, stereotyping, and signaling in applicant assessments. We interviewed 45 STEM professors. They answered qualitative open-ended interview questions, and evaluated hypothetical applicant profiles, qualitatively and quantitatively. The applicant profiles enabled a conjoint experiment with different applicant attributes varied across the profiles (i.e., publications, willingness to cooperate, network recommendation, and applicant gender), the interviewees indicating scores of selection recommendation while thinking aloud. Our findings reveal gendered arguments, i.e., questioning women potentially fueled by a perception of women’s exceptional status and perceived self-questioning of women. Furthermore, they point to gender-independent and gender-dependent success patterns, thereby to potential success factors particularly for female applicants. We contextualize and interpret our quantitative findings in light of professors’ qualitative statements.
Keywords: General Psychology

Robot leadership–Investigating human perceptions and reactions towards social robots showing leadership behaviors - Cichor, Jakub Edward; Hubner-Benz, Sylvia; Benz, Tobias; Emmerling, Franziska; Peus, Claudia (PLOS ONE)
Human-robot interaction research has shown that social robots can interact with humans in complex social situations and display leadership-related behaviors. Therefore, social robots could be able to take on leadership roles. The aim of our study was to investigate human followers’ perceptions and reactions towards robot leadership behavior, and differences based on the robot’s displayed leadership style. We implemented a robot to show either a transformational or a transactional leadership style in its speech and its movements. We presented the robot to university and executive MBA students (N = 29) and subsequently conducted semi-structured interviews and group discussions. The results of explorative coding indicated that participants differed in their perceptions and reactions based on the robot’s leadership style and based on their assumptions about robots in general. We observed that participants quickly imagined either a utopia or worried about a dystopia, depending on the robot’s leadership style and their assumptions, and that a subsequent reflection led to more nuanced views. We discuss the implications and recommendations for human-robot interaction and leadership research.
Keywords: Multidisciplinary

What predicts effectuation preferences Disentangling individual and environmental factors and illuminating decision criteria - Hubner-Benz, Sylvia; Baum, Matthias (International Journal of Entrepreneurial Venturing)
Keywords: Management of Technology and Innovation; Strategy and Management; Business and International Management

Different ways lead to ambidexterity: Configurations for team innovation across China, India, and Singapore - Deng, Wei; Hubner-Benz, Sylvia; Frese, Michael; Song, Zhaoli (Journal of International Management)
Keywords: Strategy and Management; Finance; Business and International Management

Ambivalenzkompetenz? Rückblick auf die Tagung "Katastrophen". Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert am Vortag des russischen Angriffs auf die Ukraine - Schroeter-Wittke, Harald; Breckner, Anne (Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert)

Combined Economic and Emission Dispatch of a Microgrid Considering Multiple Generators - Philipo, Godiana Hagile; Kakande, Josephine Nakato; Krauter, Stefan (Proceedings of the 2023 IEEE PES/IAS PowerAfrica Conference)

Demand side management potential of refrigeration appliances - Kakande, Josephine Nakato; Philipo, Godiana Hagile; Krauter, Stefan (Proceedings of the 2023 IEEE PES/IAS PowerAfrica Conference)

Demand-Side-Management for Optimal dispatch of an Isolated Solar Microgrid - Philipo, Godiana Hagile; Kakande, Josephine Nakato; Krauter, Stefan (Proceedings of the 2023 IEEE AFRICON, Nairobi, Kenya)

Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert

Igor Levit - No Fear! Ein Film von Regina Schilling - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik (https://www.theomag.de/145/hsw24.pdf))

A Methodical Approach to Hybrid Modelling for Contextual Anomaly Detection on Time-Series Data - Lenz, Cederic; Henke, Christian; Trächtler, Ansgar (2023 IEEE 21st International Conference on Industrial Informatics (INDIN))

Innovative self-learning disturbance compensation for straightening processes - Bathelt, Lukas; Djakow, Eugen; Henke, Christian; Trächtler, Ansgar (Materials Research Proceedings)
Abstract. To increase the sustainability of forming processes such as punch bending, homogenization of the processed semi-finished product is an essential step in the manufacturing process. High-strength wire materials are usually available as strip material before being further processed in a forming process. For storage and transport, the material is coiled onto coils and transported to the customer. During the coiling process, residual stresses and plastic deformation are introduced into the wire. Thus, the final product quality is also influenced by the geometry of the coil. Straightening machines are used in production lines to compensate for these. Once a straightening machine has been set up, the settings for the roll positions are usually not changed. As a result, there is no reaction to material fluctuations, which means that the components to be produced do not meet the dimensional accuracy requirements. This leads to an increase in the rejection rate in manufacturing processes. To reduce the rejection rate, it is necessary to enable dynamic and flexible infeed of the straightening rollers. In this context, an innovative control concept with disturbance compensation was developed for the straightening process. The disturbance compensation uses a disturbance model that predicts the change in bending curvature over the coil radius. With this prediction, the straightening machine can be adjusted specifically. The roller positions are adjusted by a subordinate position control. The additional feedback from measured geometric product properties from the following punching-bending process enables the straightening machine to be adjusted even in the case of unforeseen fluctuations in the material properties. In this way, it is possible to react to any material fluctuations as required. This novel, demand-oriented adjustment of the straightening machine is expected to result in a high increase in the efficiency of the production process and a reduction of the rejection rate.

Neuartiger Ansatz zum Richten von zwei- und dreidimensionalen Fehlern an einem Federdraht - Bathelt, Lukas; Djakow, Eugen; Dahms, Frederik; Henke, Christian; Trächtler, Ansgar; Homberg, Werner (Ilmenauer Federntag 2023: Neueste Erkenntnisse zu Funktion, Berechnung, Prüfung und Gestaltung von Federn und Werkstoffen)

Learning the Automated Setup of Profile Wrapping Lines for New Products from Few Past Setups - Koppert, Steven; Bause, Maximilian; Henke, Christian; Trächtler, Ansgar (2023 IEEE 21st International Conference on Industrial Informatics (INDIN))

Increased Sustainability in Fastener Production with the Example of Self-Piercing Rivets - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Journal of Manufacturing and Materials Processing)
The sustainability of the manufacturing industry is of special importance to increase the protection of the environment. The production of fasteners like self-piercing rivets, however, is costly, time-consuming and energy-intensive. The heat treatment and the coating, which are mandatory in conventional self-piercing rivets to achieve adequate strength, ductility and corrosion resistance, are especially crucial in this respect. Within this paper, an approach for an increase in the sustainability in fastener production is presented. The use of alternative, high strain hardening stainless steels as rivet material enables a shortening of the process chain, because post treatment of the rivets after they are formed can be omitted. As the change in rivet material and processing causes some issues along the process chain, the focus of this paper is on the holistic evaluation of the challenges within the forming of high strain hardening steel and the impact of the changed rivet properties on the joining result.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Molecular Adhesion of a Pilus‐derived Peptide Involved in Pseudomonas aeruginosa Biofilm Formation on non‐polar ZnO Surfaces - Prüßner, Tim; Meinderink, Dennis; Zhu, Siqi; Orive, Alejandro G.; Kielar, Charlotte; Huck, Marten; Steinrück, Hans-Georg; Keller, Adrian; Grundmeier, Guido (Chemistry – A European Journal)
Bacterial colonization and biofilm formation on abiotic surfaces are initiated by the adhesion of peptides and proteins. Understanding the adhesion of such peptides and proteins at a molecular level thus represents an important step toward controlling and suppressing biofilm formation on technological and medical materials. This study investigates the molecular adhesion of a pilus‐derived peptide that facilitates biofilm formation of Pseudomonas aeruginosa, a multidrug‐resistant opportunistic pathogen frequently encountered in healthcare settings. Single‐molecule force spectroscopy (SMFS) was performed on chemically etched ZnO surfaces to gather insights about peptide adsorption force and its kinetics. Metal‐free click chemistry for the fabrication of peptide‐terminated SMFS cantilevers was performed on amine‐terminated gold cantilevers and verified by X‐ray photoelectron spectroscopy (XPS) and polarization‐modulated infrared reflection absorption spectroscopy (PM‐IRRAS). Atomic force microscopy (AFM) and XPS analyses reveal stable topographies and surface chemistries of the substrates that are not affected by SMFS. Rupture events described by the worm‐like chain model (WLC) up to 600 pN were detected for the non‐polar ZnO(11‐20) surfaces. The dissociation barrier energy at zero force ΔG(0), the transition state distance xb and bound‐unbound dissociation rate at zero force koff(0) for the single crystalline substrate indicate that coordination and hydrogen bonds dominate the peptide/surface interaction.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Lithium niobate waveguide squeezer with integrated cavity length stabilisation for network applications - Stefszky, M.; vom Bruch, F.; Santandrea, M.; Ricken, R.; Quiring, V.; Eigner, C.; Herrmann, H; Silberhorn, C (Optics Express)
We report a titanium indiffused waveguide resonator featuring an integrated electro-optic modulator for cavity length stabilisation that produces close to 5 dB of squeezed light at 1550 nm (2.4 dB directly measured). The resonator is locked on resonance for tens of minutes with 70 mW of SH light incident on the cavity, demonstrating that photorefraction can be mitigated. Squeezed light production concurrent with cavity length stabilisation utilising the integrated EOM is demonstrated. The device demonstrates the suitability of this platform for squeezed light generation in network applications, where stabilisation to the reference field is typically necessary.
Keywords: Atomic and Molecular Physics; and Optics

Ibn Khaldûn and the Political Economy of Communication in the Age of Digital Capitalism - Fuchs, Christian (Critical Sociology)

Analysis and Optimization of Joint Formation in Hybrid Compression Molding - Lückenkötter, Julian; Aydin, Simon; Marten, Thorsten; Tröster, Thomas

Evidence-based practices in teaching - Rybska, Eliza; Dudziak, Renata; Pollmeier, Pascal (Problemy Wczesnej Edukacji)
This article presents the results of the implementation of the Erasmus Plus project (KA203 financed by the European Union, contract number 2019-1-NL01-KA203-060339) Research in Teacher Education (RiTE). The aim of the project was to promote and facilitate pre-service teachers to create and undertake evidence-based practices in teaching science, technology, engineering, and mathematics (STEM). In the RiTE project, pre-service teachers were encouraged to use evidence from educational and scientific research and to experiment and introduce didactic innovations in teaching and learning processes. Although it has its justification in the tradition of thinking about science, evidence-based practice is not yet consciously applied in school practice. In the article, we present both the theoretical framework for such practices, and the results of qualitative research – an analysis of interviews conducted with students, future teachers, and novice teachers involved in the project. The presented results show changes in the context of an understanding of evidence and what evidence-based practices are in the teaching process and the vision of such teaching presented by the respondents.

Wer übernimmt Verantwortung für Inklusion? - Kottmann, Brigitte; Lütje-Klose, Birgit; Neumann, Phillip (Zeitschrift für Heilpädagogik)
Keywords: Inklusion; Bildungspolitik; Schulentwicklung; Sonderpädagogik

Elektrooptischer Balun und System zur Generierung eines pseudodifferentiellen Signals aufweisend einen solchen elektrooptischen Balun - Kruse, Stephan; Scheytt, J. Christoph
Die Erfindung betrifft einen elektrooptischen Balun, wobei der elektrooptische Balun einen Eingang für ein optisches Eingangssignal (Ein(t)) aufweist, wobei der elektrooptische Balun weiterhin ein 1x2 Multimodeninterferometer (1x2 MMI) und einen Phasenschieber (Δϕ) aufweist, wobei das 1x2 Multimodeninterferometer (1x2 MMI) mit dem Eingangssignal im Betrieb versorgbar ist, wobei der elektrooptische Balun weiterhin ein 2x4 Multimodeninterferometer (2x4 MMI) aufweist, wobei das 2x4 Multimodeninterferometer (2x4 MMI) mit den Ausgangsarmen des 1x2 Multimodeninterferometer (1x2 MMI) verbunden ist, wobei der Phasenschieber (Δϕ) in einem Ausgangsarm des 1x2 Multimodeninterferometer (1x2 MMI) angeordnet ist, wobei im Betrieb an zwei Ausgängen (Eout,1 (t), Eout,4(t)) des 2x4 Multimodeninterferometers (2x4 MMI) ein quasi differentielles optisches Signal anliegt, das mittels einer jeweiligen Photodiode (PD1, PD2) und einem differentiellen Schaltkreis in ein DC-freies elektrisches Signal (Vout) überführt werden kann. Weiterhin betrifft die Erfindung ein System zur Generierung eines pseudeodifferentiellen Signals, aufweisend einen elektrooptischen Balun sowie einen optischen Strahlteiler (OS) sowie einen dual output carrier injection Mach Zehnder Modulator (MZM), wobei der optische Strahlteiler (OS) ein Eingangssignal (IIN) in einen ersten Teil (n) und einen zweiten Teil (1-n) aufteilt, wobei der zweite Teil (1-n) als Eingangssignal (Ein(t)) im Betrieb auf den Eingang des elektrooptischen Baluns geführt wird, wobei der erste Teil (n) im Betrieb als Eingangssignal dem dual output carrier injection Mach Zehnder Modulator (MZM) zugeführt wird, wobei das quasi differentielle elektrische Signal (I1, I2) der Photodioden (PD1, PD2) im Betrieb zur Ansteuerung des dual output carrier injection Mach Zehnder Modulator (MZM) in push pull Konfiguration verwendet wird.

Elektrooptischer Mischer - Kruse, Stephan; Scheytt, J. Christoph
Die Erfindung betrifft einen elektrooptischen Mischer (1) mit elektrischem Ausgang, aufweisend: • eine Photodiode (PD), • einen ersten Anschluss, • einen zweiten Anschluss, • wobei die Anschlüsse eine erste Spannungsversorgung (V1) und eine zweite Spannungsversorgung (V2) oder eine erste Stromversorgung (I1) und eine zweite Stromversorgung (I2) anschließbar ist, • einen Anschluss für ein Kleinsignal-Massepotential, • ein erstes Teilanpassungsnetzwerk (Z2, Z4), welches auf der Anodenseite der Photodiode (PD) angeordnet ist, wobei ein Teil des ersten Teilanpassungsnetzwerkes (Z2) mit dem Anschluss für die zweite Spannungsversorgung (V2) schaltbar (S2) verbindbar ist, und wobei ein anderer Teil des ersten Teilanpassungsnetzwerkes (Z4) mit dem Anschluss für das Kleinsignal-Massepotential schaltbar (S2') verbindbar ist, • ein zweites Teilanpassungsnetzwerk (Z1, Z3), welches auf der Kathodenseite der Photodiode (PD) angeordnet ist, wobei ein Teil des zweiten Teilanpassungsnetzwerkes (Z1) mit dem Anschluss für die erste Spannungsversorgung (V1) schaltbar (S1) verbindbar ist, und wobei ein anderer Teil des zweiten Teilanpassungsnetzwerkes (Z3) mit dem Anschluss für das Kleinsignal-Massepotential schaltbar (S1') verbindbar ist, • ein erstes entkoppelndes Element (C1) angeordnet auf der Kathodenseite und ein zweites entkoppelndes Element (C2) angeordnet auf der Anodenseite der Photodiode (PD), • wobei zwischen den von der Photodiode (PD) abgewandten Seiten des ersten entkoppelnden Elementes (C1) und des zweiten entkoppelnden Elementes (C2) im Betrieb einelektrisches Ausgangssignal bereitgestellt werden kann.

ENHANCED PLL CIRCUIT - Iftekhar, Mohammed; Scheytt, J. Christoph

Photonic Quantum Enhanced Radar Systems - Kruse, Stephan

Einfluss von Infrarotschweißprozessparametern auf die quasistatische und zyklische Belastbarkeit von technischen glasfaserverstärkten Thermoplasten - Gevers, Karina; Töws, P.; Schraa, L.; Decker, J.; Schöppner, Volker; Uhlig, K.; Stommel, M. (11. Landshuter Leichtbau-Colloquium)

A NEW APPROACH FOR THE LOCAL DETERMINATION OF ENERGY INPUT IN CO-ROTATING TWIN SCREW EXTRUDERS BASED ON SCREW TORSION - Schöppner, Volker; Austermeier, Laura; Nordieker, A.

Development Of An Asymmetric Torque Model For The Two Screws Of A Twin Screw Extruder - Schöppner, Volker; Austermeier, Laura; Alsoud, A.

Auswirkungen unterschiedlicher Erwärmstrategien auf infraroterwärmte Polyphthalamide - Schöppner, Volker; Gevers, Karina; Schraa, L.; Töws, P.; Uhlig, K.; Stommel, M.; Decker, J. (Joining Plastics)

Devulkanisation schwefelvernetzender Elastomere im halbleitergestützten Mikrowellenverfahren - Schöppner, Volker; Petzke, J.

Numerical investigations of new low‐order explicit last stage diagonal implicit Runge–Kutta schemes with the finite‐element method - Westermann, Hendrik; Mahnken, Rolf (PAMM)
Abstract Initial value problems can be solved efficiently by means of Runge–Kutta algorithms with adaptive step size control. Diagonally implicit Runge–Kutta (DIRK) methods are the most popular class among the diverse family of Runge–Kutta algorithms. In this paper, the novel class of low‐order explicit last‐stage diagonally implicit Runge–Kutta (ELDIRK) methods are explored, which combine implicit schemes with an additional explicit evaluation as an explicit last stage. ELDIRK Butcher tableaus are used to control embedded RK methods to obtain solutions of different orders. The lower‐order solution is obtained by classical implicit RK stages and the higher‐order solution is obtained by additional explicit evaluation. As a result, a significant reduction in computational cost is achieved by skipping the iterative solution of nonlinear systems for the additional step. The examination of the heat problem and the use of the innovative Butcher tableau in the finite‐element method are the main contributions of this work. Thus, it is possible to establish adaptive step size control for the new low‐order embedded methods based on an empirical method for error estimation. Two‐dimensional simulations are used to show an appropriate algorithm for the ELDIRK schemes. The new Runge–Kutta schemes' predictions of higher‐order convergence are confirmed, and their successful outcomes are illustrated.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

On the accuracy, stability and computational efficiency of explicit last-stage diagonally implicit Runge–Kutta methods (ELDIRK) for the adaptive solution of phase-field problems - Westermann, Hendrik; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Multiphase elasto-plastic mean-field homogenisation and its consistent linearisation - Lenz, Peter; Kreutzheide, Phil; Mahnken, Rolf (Computers & Structures)
Keywords: Computer Science Applications; Mechanical Engineering; General Materials Science; Modeling and Simulation; Civil and Structural Engineering

No effects of different perturbations on the performance in a mental body-rotation task (MBRT) with egocentric perspective transformations and object-based transformations - Budde, Kirsten; Weigelt, Matthias (Human Movement Science)
The present study investigates participants' performance in two different mental body-rotation tasks (MBRTs) under conditions in which dynamic stability is challenged in two different balancing conditions: active balance control (Experiment 1), where participants actively maneuver, and re-active balance control (Experiment 2), where participants react to an external perturbation. The two MBRTs induced either an object-based spatial transformation (based on a same-different judgment) or an egocentric transformation (based on a left-right judgment). In Experiment 1, 48 participants were tested while standing on an even ground (low balancing requirements) or on a balance board (high balancing requirements). In Experiment 2, 32 participants performed while either standing still on a vibration plate or with the vibration plate moving in a low (20 Hz) or high (180 Hz) frequency. In both experiments, the results for response time and response error revealed effects of rotation angle and type of task. An effect of balancing condition was only observed for response error in Experiment 1. More precisely, response times and response errors increased for higher rotation angles. Also, performance was better for egocentric than for object-based spatial transformations. However, the different challenges to dynamic stability in Experiments 1 and 2 did not influence performance in the two MBRTs (except for response errors in Experiment 1) nor in a control condition (Experiment 1) without mental rotation.
Keywords: Mental rotation; Balance control; Perturbation; Embodiment

Rezension: Erika Thomalla: Anwälte des Autors. Zur Geschichte der Herausgeberschaft im 18. und 19. Jahrhundert, Göttingen: Wallstein 2020 und Ines Barner: Von anderer Hand. Praktiken des Schreibens zwischen Autor und Lektor, Göttingen: Wallstein 2021 - Spener, Anna Maria; Heimgartner, Stephanie (Sprache und Literatur)

Investigation of the Volume Flow in the FFF Process as an Influencing Factor on the Resulting Orientation of Thermally Conductive Filler Particles - Moritzer, Elmar; Elsner, Christian Lennart; Deupmann, K.

Investigation of the influence of screw geometry on the resulting melt quality for cast film extrusion - Schöppner, Volker; Trienens, Dorte

Großflächig, komplex? InMould-Plasma ist die Lösung! - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Rauen, Dennis; Kolbe, B.; Schlee, H.; Hokamp, C. (Kunststoffe)

Goodbye Hot Spots - with No Extra Energy Expenditure - Moritzer, Elmar; Kartelmeyer, Stephan; Kreamer, Dennis; Jaroschek, Christoph (Plastics Insights)

Hauptsache, die Wellenlänge stimmt - Schöppner, Volker; Frank, Maximilian; Schall, Christoph Wilhelm Theodor (Kunststoffe)

Hotspots ade - ohne Extra-Energieaufwand - Moritzer, Elmar; Kartelmeyer, Stephan; Kraemer, Dennis; Jaroschek, Christoph (Kunststoffe)

Optimization of additively manufactured parts for direct screwing - Moritzer, Elmar; Held, Christian

Optimisation of the Simulation of Rubber Extrusion dies by means of the Integration of empirically determined characteristic Maps - Schöppner, Volker; Kleinschmidt, Dennis; Hopmann, C.; Wiesel, C.; Nillius, U.; Schön, M.; Limper, A. (KGK Kautschuk Gummi Kunststoffe)

Mischmaterialschweißen von PC/ABS und PMMA beim Warmgasstumpfschweißen mit Runddüsen - Schöppner, Volker; Gevers, Karina; Albrecht, M.; Seefried, A.

Microwave Heating of Rubber Extrudates - Petzke, J.; Kleinschmidt, Dennis; Schöppner, Volker

Konturnah kühlen für wenig Geld - Moritzer, Elmar; Kartelmeyer, Stephan; Kringe, Roberg; Jaroschek, Christoph (Kunststoffe)

Methoden zur Förderung von Kompetenzen für eine demokratische Kultur - Schriftliche Reflexionen von Lehramtsstudierenden aus bildungswissenschaftlichen Seminaren - Wehde, Janis; Bloh, Bea

Wie war das damals? Oral history und Zeitzeug:innenbefragung - Diederich, Julia ((Über-)Leben im Nationalsozialismus)

Incremental permutation feature importance (iPFI): towards online explanations on data streams - Fumagalli, Fabian; Muschalik, Maximilian; Hüllermeier, Eyke; Hammer, Barbara (Machine Learning)
Abstract Explainable artificial intelligence has mainly focused on static learning scenarios so far. We are interested in dynamic scenarios where data is sampled progressively, and learning is done in an incremental rather than a batch mode. We seek efficient incremental algorithms for computing feature importance (FI). Permutation feature importance (PFI) is a well-established model-agnostic measure to obtain global FI based on feature marginalization of absent features. We propose an efficient, model-agnostic algorithm called iPFI to estimate this measure incrementally and under dynamic modeling conditions including concept drift. We prove theoretical guarantees on the approximation quality in terms of expectation and variance. To validate our theoretical findings and the efficacy of our approaches in incremental scenarios dealing with streaming data rather than traditional batch settings, we conduct multiple experimental studies on benchmark data with and without concept drift.
Keywords: Artificial Intelligence; Software

Single-shot spatial instability and electric control of polariton condensates at room temperature - Gao, Ying; Ma, Xuekai; Zhai, Xiaokun; Xing, Chunzi; Gao, Meini; Dai, Haitao; Wu, Hao; Liu, Tong; Ren, Yuan; Wang, Xiao; Pan, Anlian; Hu, Wei; et al. (Physical Review B)

“I do not know! but why?” — Local model-agnostic example-based explanations of reject - Artelt, André; Visser, Roel; Hammer, Barbara (Neurocomputing)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications

Threshold photoelectron spectroscopy and dissociative photoionization of benzonitrile - Kamer, Jerry; Schleier, Domenik; Donker, Merel; Hemberger, Patrick; Bodi, Andras; Bouwman, Jordy (Physical Chemistry Chemical Physics)
The seven parallel dissociative ionization channels of benzonitrile yield highly stable fragment ions with commensurate abundance, underlining the potential role of the benzonitrile cation as hub species in the interstellar medium.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy